Analisa Desain, Konsep, dan Karakteristik Sistem Transfer Daya Nirkabel - Ike Yuni Wulandari (Fakultas Teknik, 2020)
In the current era of the industrial revolution 4.0, the need for time, labor, and cost efficiency is a basic requirement for human life, especially regarding electrical energy sources. The supply of commercial electricity is still using electricity cables to deliver electricity to the load. Therefore, one of the ways of sending or transferring electrical power that continues to be developed today is wireless electricity transfer. The wireless transfer of electric power has several advantages compared to the use of cables, which can increase the convenience in the use of electrical equipment and can reduce the amount of electronic waste. This research will study the techniques or methods of near-field wireless energy transfer systems, namely the inductive coupling method, the magnetic resonance coupling method and the capacitive coupling method. The results of this study propose an optimal modeling of wireless power transfer so that results and quality are better, taking into account the distance between the sender and receiver because the work efficiency of wireless power transfer decreases with respect to distance. And the signal transmission frequency is low for inductive coupling, while the resulting frequency will be high on magnetic resonance coupling and capacitive coupling.